The Invisible War: A Portrait Of Structural Racism and Mental Health in the Life of a Formerly Incarcerated U.S. Born Africana Man - Kyles, Tarell C (2017)
This study examines the ways in which a formerly incarcerated U.S. born Africana man age 47 perceives, interprets, and copes with being criminalized and disenfranchised by interacting institutions which support white domination and black subordination. The focal point of inquiry is an analysis of the reverberating mental health impacts of structural racism via the criminal justice system. Utilizing portraiture and person-environment fit theory, this study presents a multivocal portrait of a man, his life, his family, and his community impacted by the stress/strain of navigating environments characterized by structural racism and inequality. The study seeks to add to the relevant bodies of knowledge a more nuanced and contextual examination of the negative mental health impacts of structural racism via the criminal justice system, which will inform policy and advocacy issues, as well as future interventions designed to empower historically marginalized populations in the U.S